1963
DOI: 10.1128/jb.86.3.536-543.1963
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Aspects of Antimicrobial Antibiosis Iii

Abstract: College, New York, N.Y.) AND GEORGE B. CHAP-MAN. Cytological aspects of antimicrobial antibiosis. III. Cytologically distinguishable stages in antibiotic action of colistin sulfate on Escherichia coli. J. Bacteriol. 86:536-543. 1963.-Broth cultures of Escherichia coli were subjected to a constant concentration of colistin sulfate for varying periods of time. Controls and treated cells were fixed, dehydrated, and embedded in 536

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It has been reported that Acinetobacter are short rods in the logarithmic phase of growth but often become more coccoid in the stationary phase 26 . In this study, the short bacilli tended to be more damaged than the long bacilli, suggesting that the growth phase may be related to the onset of initial damage caused by colistin 27 , but further study is needed.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that Acinetobacter are short rods in the logarithmic phase of growth but often become more coccoid in the stationary phase 26 . In this study, the short bacilli tended to be more damaged than the long bacilli, suggesting that the growth phase may be related to the onset of initial damage caused by colistin 27 , but further study is needed.…”
Section: Discussionmentioning
confidence: 78%
“…4:671, 1958. ) investigation, however, it is now apparent that the distinction is not completely valid, for mesosomes have been described even in E. coli (45,46). It seems, nevertheless, that they are rare under normal conditions of growth in enterobacteria, whereas they are abundant and readily demonstrated in many gram-positive microorganisms, including streptococci (Fig.…”
Section: Speculationmentioning
confidence: 99%